Caribbean Report 01-08-1990 - Whitehorne, Pat (anchor); Mathur, Ira (correspondent); Adie, Kate (correspondent); Crosskill, Hugh (correspondent); Madeira, Laura Lee (interviewee); Basdeo, Sahadeo (interviewee); Pantin, Dennis (interviewee) (The British Broadcasting Corporation, 1990)
The Muslim gunmen holding forty hostages at Parliament building and the television station in Port of Spain have surrendered and the hostages are being released. Ira Mathur (correspondent) speaks on the release of the women parliamentarians, Gloria Henry and Jennifer Johnson at Parliament building, the mood of the population in Port of Spain and reported casualties at the city's hospital. Kate Adie (correspondent) describes in detail the surrender of the fifty insurgents who were later driven away in army vehicles. Laura Lee Madeira, daughter of Jones P. Madeira, hostage and journalist is thankful for the release of her father and Trinidadians voice strong disapproval of the coup. Much thought provoking issues come up with the coup d'etat including the fragility of Caribbean democracies and the impact of the International Monetary Fund and the World Bank on small economies. Sahadeo Basdeo,Trinidad and Tobago Foreign Affairs Minister and Dennis Pantin, vice-president of the Association of Caribbean Economist speak on the issues.
1. Headlines: Pat Whitehorne (anchor)reports on the release of the hostages in Port of Spain, Trinidad and Tobago (00:00-00:32)
2. Pat Whitehorne (anchor)reports on the surrender of the Muslimeen insurgents and the release of the hostages (00:33-00:58)
3. Interview with Ira Mathur (correspondent) on the release of the hostages at Parliament building, the mood of the populace in the city and reported caualities (00:59-03:02)
4. Katie Adie (correspondent) reports on the surrender of the insurgents in Port of Spain (03:03-04:32)
Keywords: Muslims, Black -- Trinidad and Tobago.; Trinidad and Tobago -- History -- Attempted coup, 1990.; Coups d'etat -- Trinidad and Tobago.; Islam and State -- Trinidad and Tobago.; Structural adjustment (Economic policy) -- Trinidad and Tobago.; Jamaat-al-Muslimeen.